Hybrid and Blended Learning Models: Innovations, Challenges, and Future Directions in Education - Mulenga, Robert; Shilongo, Helvi (Tecno Scientifica Publisher, 2025)
The rise of hybrid and blended learning models has transformed educational practices, combining the strengths of in-person and online learning. This review explores recent innovations, challenges, and future directions in these models. Technological advancements such as artificial intelligence (AI), adaptive learning platforms, and virtual reality (VR) are reshaping the delivery of hybrid education by offering personalized learning experiences, automating assessments, and creating interactive simulations. Pedagogical shifts, including flipped classrooms and competency-based education, are becoming central to hybrid learning environments, emphasizing student-centered approaches and maximizing active engagement. The integration of microlearning and modular course design further enhances flexibility, catering to diverse learning styles and paces. Despite these innovations, significant challenges remain. Issues of equity and access persist, with underprivileged students facing barriers due to lack of internet connectivity and digital resources. Additionally, instructors face increased workloads and must adapt to new technologies, often requiring further training to manage hybrid classrooms effectively. Maintaining student engagement, particularly in asynchronous settings, also presents difficulties. The review highlights best practices, such as the use of interactive learning strategies, continuous assessment, and offering flexible learning paths to support student success in hybrid settings. Looking forward, the future of hybrid and blended learning points towards greater personalization through AI, enhanced sustainability by reducing the reliance on physical infrastructure, and the integration of immersive technologies like augmented and virtual reality. These advancements hold the potential to revolutionize hybrid learning, making education more accessible, engaging, and adaptable to a variety of learning environments.